Vibrational spectra of Sn2TiO4 - Baran, Enrique José (2010)
The infrared and Raman spectra of the recently synthesized tin(II) titanate, Sn2TiO4, were recorded and briefly discussed on the basis of its structural peculiarities. © 2009 Elsevier B.V. All rights reserved.